Aғылшын жəне қазақ тілдеріндегі фразеологиялық теңеулердің концептілік құрылымы - Нургужина, С.Н.; Габдешева, А.Е. (My University, 2016)
The phraseology of each language covered by mentality, the psychology and culture of the nation. The relevance of this article to define these characteristics and thus generate interest. Thus the goal is to identify the differences and similarities between the phraseology of the Kazakh and English languages. To achieve this goal has been used linguocultural method of analysis. As a result, it determined peculiarities of phraseology of these languages.
Keywords: linguistics; linguistics; verbal idioms; sustainable combination of words